Inferior Mesenteric Artery Associated Type II Endoleaks: Are They Predictable? - Jalil, Harun; Mahmood, Syed; Zaman, Iftikhar; Osman, Asaad; Mustafa, Syed; Saeed, Abdullah (The Arab Journal of Interventional Radiology, 2021)
Purpose This study aims to evaluate the relationship between inferior mesenteric artery (IMA) diameter and risk of type II endoleak.Subjects and Methods: A retrospective study design to review all EVARs performed over a 4-year period at a tertiary care center. Out of the total cohort of 400 patients who underwent EVAR, 41 patients (10.3%) developed type II endoleak. The mean IMA ostial diameter for patients with type II endoleak secondary to IMA contributories was 4mm, while the mean IMA diameter for patients with lumbar arteries contributing to the type II endoleak was 3.7mm.Results Statistical analysis using a paired t-test did not show a statistically significant difference in the IMA ostial diameter between the two groups.Conclusion There is no significant correlation between preprocedural IMA ostium diameter and type II endoleak development and hence, preprocedural IMA embolization is not an appropriate prophylactic management strategy.
Keywords: abdominal aortic; endoleak; vascular interventional